Antibacterial drug utilization study in patient of sepsis due to Staphylococcus aureus - Vaidya, Dhruti; Trivedi, Niyati; Patel, KuntalKumar H. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Sepsis is the most common and highly fatal clinical syndrome due to infection. Gram-positive organisms as a cause of sepsis have increased in frequency over time more common than gram-negative infections. S. aureus bacteremia (SAB) is one of the most prevalent and difficult to treat infections associated with significant morbidity and mortality. Aim was to study antibacterial drug utility, sensitivity and resistance pattern of antibacterial drugs in S. aureus infective septic patient in medicine department. Methods: A prospective observational study was done in medicine department of SSG hospital, Vadodara over a period of 9 months. Results: Total 50 S. aureus were tested for their sensitivity and resistance pattern towards ten antibacterial agents in microbiology department by disc diffusion method. The antibiogram of S. aureus indicated widespread resistance antibacterial agent ranging from a minimum resistant to vancomycin (4%) to a maximum of 90% against penicillin G. Total 142 antibacterial agents were prescribed in 50 patients. Metronidazole, ceftriaxone and piptaz were the most frequently prescribed antibacterial agents with DDD/1000 patient days 2.44, 3.55 and 2.62 respectively. 30 out of 50 patients needed a change in antibacterial agents during their course of treatment either due to antibacterial agent failure or after culture sensitivity report. 60% of the patients were prescribed ≥3 antibacterial agents at any point of time during treatment. Mean DOT/LOT was 2.22±0.84. Conclusions: There is a need of antibacterial agent usage guidelines and restriction policies for the rational prescribing of antibacterial agent in critically ill patients.